DEVELOPMENT OF THE LABOR MARKET IN THE CONDITIONS OF FORMATION OF THE DIGITAL ECONOMY - M. V. Rybkina; M. V. Kangro; E. V. Pirogova (Вестник университета)
The key problems of the development of the labor market in the conditions of formation of the digital economy have been considered. The digital economy dictates to all countries of the world the paradigm of development of new directions in the economic sphere. The influence of the digital economy on the state of the labor market has been investigated, a number of its new features has been shown. The number of people employed in the economy by gender and status has been analyzed, and it has been shown, how changes, related to the digital economy, affect the issues of retraining and personnel training. The importance of implementing information and communication technologies in modern Russia, taking into account the needs of the labor market, has been emphasized. Measures have been proposed to solve problems, identified by the results of the study.